Functional near‐infrared spectroscopy measures of neural activity in children with and without developmental language disorder during a working memory task. Issue 2 (27th January 2023) - Hancock, Allison S.; Warren, Christopher M.; Barrett, Tyson S.; Bolton, David A. E.; Gillam, Ronald B.
Abstract: Introduction: Children with developmental language disorder (DLD) exhibit cognitive deficits that interfere with their ability to learn language. Little is known about the functional neuroanatomical differences between children developing typically (TD) and children with DLD. Methods: Using functional near‐infrared spectroscopy, we recorded oxygenated hemoglobin (O2 hb) concentration values associated with neural activity in children with and without DLD during an auditory N ‐back task that included 0‐back, 1‐back, and 2‐back conditions. Analyses focused on the left dorsolateral prefrontal cortex (DLPFC) and left inferior parietal lobule (IPL). Multilevel models were constructed with accuracy, response time, and O2 hb as outcome measures, with 0‐back outcomes as fixed effects to control for sustained attention. Results: Children with DLD were significantly less accurate than their TD peers at both the 1‐back and 2‐back tasks, and they demonstrated slower response times during 2‐back. In addition, children in the TD group demonstrated significantly greater sensitivity to increased task difficulty, showing increased O2 hb to the IPL during 1‐back and to the DLPFC during the 2‐back, whereas the DLD group did not. A secondary analysis revealed that higher O2 hb in the DLPFC predicted better task accuracy across groups. Conclusion: When task difficulty increased, children with DLD failed to recruit the DLPFC for monitoring information and the IPL for processing information. Reduced memory capacity and reduced engagement likely contribute to the language learning difficulties of children with DLD. Abstract : Using fNIRS, we recorded oxygenated hemoglobin (O2 hb) concentration values in children with and without DLD during an auditory N ‐back task that included 0‐back, 1‐back, and 2‐back conditions. Typically developing children displayed sensitivity to working memory load in the frontal and parietal areas. Children with developmental language disorders demonstrated difficulties in engaging frontal parietal areas related to working memory. Higher O2 hb concentration values in the left dorsolateral prefrontal cortex predicted better task accuracy across groups.